PENGARUH KUALITAS AUDIT TERHADAP MANAJEMEN LABA MELALUI AKTIVITAS RIIL - Nico Radityo Boedhi; Dewi Ratnaningsih (Faculty of Business and Economics Universitas Atma Jaya Yogyakarta, 2015)
This study examines the impact of audit quality on Real Earnings Management (REM). Real earnings management is defined as management actions that deviate from normal business practices, undertaken withthe primary objective of meeting certain earnings thresholds (Roychowdhury, 2006). One proxy is taken for real earnings management, while abnormal operating cash flows and proxy for audit quality are taken as the size of audit firm. Research samples are selected from the population of manufacturing companies listed in Bursa Efek Indonesia from year 2007 to 2011. Sample criteria is companies which have strong incentive to engage in real earnings management and 126 companies are selected. Multiple Regression Model has been applied for data analysis. It is found that impact of audit quality on real earnings management is positive. This result concludes that audit quality is not a warranty that a company’s financial statement is free from earnings management.Keywords: audit quality, earnings management, real earnings management, abnormal cash flow operation.